The Influence of Organizational Learning and Work Motivation on Employee Performance as mediated by Job Satisfaction - Cahyanto, Fernando Oktavian; Nurhayati, Mafizatun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Objectives: The purpose of this research is to analyze the effect of organizational learning and work motivation on employee performance mediated by job satisfaction at BPJS Ketenagakerjaan Rawamangun Branch. Methodology: The data analysis method employed in this research is Partial Least Squares (PLS). Finding The outcomes of this research can be summarized as follows: organizational learning, work motivation and job satisfaction show a positive and significant impact on Employee Performance. Both organizational learning and work motivation show a positive and significant impact on job satisfaction. Job satisfaction functions as a mediator, Organizational learning has a positive and significant effect on employee performance, mediated by job satisfaction. And Work motivation has a positive and significant effect on employee performance, mediated by job satisfaction.